EFEKTIFITAS JUICE MENTIMUN (CUCUMIS SATIVUS LINN) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Suryono, Suryono; Suyanto, Agus (Akademi Keperawatan Pamenang, 2011)
Hypertension is a persistent increase in blood pressure above normal limits agreed upon, namely 90 mm Hg diastolic or 140 mmHg systolic. Lifestyle, environmental factors, uncontrolled eating, obesity, high stressors and lack of exercise is an early pioneer of high blood pressure. This study aims to determine the effectiveness of cucumber to reduce hypertension.In this study population are people who suffer from hypertension, some 20 people, the sample is some people who suffer from hypertension in the village of Brenggolo. This research design is experimental by design Pre One group pre-post test design with no comparison group. Calculations carried out from pre and post test and then taken the average value and deviation standart. From this study, the reduction of hypertension with significant levels of 0,000 hypertensive patients with total degree one as much as 100% or 20 respondents pendrita hypertension. including pre-hypertension is as much as 12 respondents (60%), and a small portion of respondents who included first-degree hypertension are there three respondents (15%) and there are respondents who included the normal five respondents (25%)From the above description can be concluded that the cucumber is effective to reduce hypertension in the village Brenggolo.